Dendritic cell PIK3C3/VPS34 controls the pathogenicity of CNS autoimmunity independently of LC3-associated phagocytosis. Issue 1 (2nd January 2022) - Yang, Guan; Postoak, J. Luke; Song, Wenqiang; Martinez, Jennifer; Zhang, Jianhua; Wu, Lan; Van Kaer, Luc
ABSTRACT: PIK3C3/VPS34 is a key player in macroautophagy/autophagy and MAP1LC3/LC3-associated phagocytosis (LAP), which play critical roles in dendritic cell (DC) function. In this study, we assessed the contribution of PIK3C3 to DC function during experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS). We found that Pik3c3 -deficient DCs exhibit attenuated capacity to reactivate encephalitogenic T cells in the central nervous system, leading to reduced incidence and severity of EAE in DC-specific Pik3c3 -deficient mice. Additionally, animals with a DC-specific deficiency in Rb1cc1/Fip200 but not Rubcn were protected against EAE, suggesting that the EAE phenotype of DC-specific Pik3c3 -deficient mice is due to defective canonical autophagy rather than LAP. Collectively, our studies have revealed a critical role of PIK3C3 in DC function and the pathogenicity of these cells during EAE, with important implications for the development of immunotherapies for autoimmune diseases such as MS. Abbreviations: ATG: autophagy-related; CNS: central nervous system; DC: dendritic cell; DEG: differentially expressed gene; EAE: experimental autoimmune encephalomyelitis; LAP: LC3-associated phagocytosis; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MHC: major histocompatibility complex; MOG: myelin oligodendrocyte glycoprotein; MS: multiple sclerosis; PIK3C3/VPS34: phosphatidylinositol 3-kinase catalytic subunit type 3; ROS: reactive oxygen species